STUDY ON THE CORROSION RESISTANCE CHARACTERISTICS OF n-TiO2/Al2O3 REINFORCED HYBRID Mg COMPOSITES - V.K Neela Murali; M.S Starvin (Journal of the Chilean Chemical Society, 2023)
The Mg based composites with the element addition of 3Zn, 0.5Mn and the reinforcement of ceramic particles nanoTiO2 and Al2O3 are added to form an Mg- hybrid composites through powder metallurgy method. The examination is mainly concentrated on the effect of multi ceramic particles such as nanoTiO2 and Al2O3 inclusion in the composite matrix for the characteristics of hardness, tensile strength, wear and corrosion. Optical and scanning electron microscopy are used for the micro structural variation. X-ray diffraction is used to analysis the various phases available in the hybrid composites matrix. Many intermetallic phase are formed during heat treatment process which reduces the porosity and increases density and corrosion resistance of the composites. The hard ceramic particles inclusion, hot extrusion process and heat treatment or stress-relieving mechanism enhances the above said properties of the prepared hybrid composites.